2022
DOI: 10.1155/2022/7288788
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Effectiveness of Music Therapy on Mental Health of College Students

Abstract: Music therapy is a relatively mature marginal subject at present, and it is also a relatively common treatment method. This kind of treatment can better help college students get rid of bad psychology and guide their psychology to develop in a healthy direction. Mental health is one of the important indicators to measure the comprehensiveness of human quality and plays an important role in the sustainable development of human beings. Music therapy plays a very important role in college students’ mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…In Peru there is already evidence of the benefits of music therapy in university students who improved significantly (stress reduction, better concentration, good academic performance, relaxation, better self-esteem, self-control, good quality interpersonal relationships) [29]. Music therapy is observed as a marginal subject, but it is known more as an alternative therapy method which is helping university students in mental health [30].…”
Section: Introductionmentioning
confidence: 99%
“…In Peru there is already evidence of the benefits of music therapy in university students who improved significantly (stress reduction, better concentration, good academic performance, relaxation, better self-esteem, self-control, good quality interpersonal relationships) [29]. Music therapy is observed as a marginal subject, but it is known more as an alternative therapy method which is helping university students in mental health [30].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%